Scrum Methodology: An ally in the implementation of LGPD (Research, Society and Development, 2023)
The evolution of the internet has generated a growing demand for regulation in order to protect the rights of users and the physical world. In Brazil, the Brazilian Civil Rights Framework for the Internet and the General Data Protection Law (LGPD) establish standards and guarantee to ensure freedom, privacy and responsibility in the use of the network. This article examines how the Scrum Methodology, an agile method of project management, can be an efficient solution for implementation and awareness of the LGPD in organizations. The bibliographic research used as the basis for this article encompasses software engineering concepts, project management methods and processes, highlighting the versatility and efficiency of Scrum in solving complex problems and adapting to constant changes. The adoption of Scrum can assist organizations in the implementation of the LGPD, providing greater agility and adaptability to legal requirements. This article addresses the importance of regulations, such as the Marco Civil da Internet and the LGPD, to guarantee the rights of users and the protection of the physical world. In addition, it proposes the Scrum Methodology as an efficient and versatile approach to the implementation and promotion of awareness about the LGPD in organizations, based on a bibliographic research that involves concepts of software engineering and project management.